Evaluating Criteria of Ecological Politics Effectiveness as a Necessary Determinant of Legal Bases of its Realization: Example of Ukrainian Realities - Vlasenko, Yuliia; Shokha, Tetiana; Sharaievska, Tetiana (European Journal of Sustainable Development, 2020)
The present paper seeks to discuss key challenges academics and practitioners face in their attempts to evaluate effectiveness of ecological policies. It summarizes and describes existing effectiveness criteria attributed to a certain policy itself, as well as suggests some external casual factors that are likely to moderate its effectiveness overtime. It further analysis major ecological policies in Ukraine and evaluation of its effectiveness. Finally, it suggests future changes that should be made in Ukrainian legislative acts to enable their effective implementation and pivotal shift in the mindset of its society. Keywords: Ecological politics, policy effectiveness, effectiveness criteria, evaluation methodology